Evaluación del bienestar animal de cerdos en ceba alojados en sistema de cama profunda - Feijoó Sánchez, John Rolando (2014)
The present PhD thesis "Evaluation of the welfare of fattening pigs housed in deep litter system" took place in the province of El Oro, Canton Piñas, generally aimed to assess animal welfare in fattening pigs using the breeding system in deep bed, the specific objectives were 1. Evaluate biological indices deep bed system compared to the traditional such as days to slaughter age production cycle, average weight at slaughter, mortality, daily feed intake kg / day, feed conversion. Two. Determine the ammonia level in the environment and the environmental impact caused by both animal production systems. Three. Determine the cost - benefit by comparing the deep litter system with traditional method in pens. April. Determine the level of aggressive behavior. For this we implemented two breeding systems, deep litter system compared to the traditional system. the results showed that there was a better productive performance in animals with deep litter system, in addition, animal welfare was better, there was a lower incidence of diseases and disorders.